Fa’āliyah Namūżaj Taqwῑm at-Tanāquḍ fῑ Taḥsῑn Jaudah Ta’lῑm al-Lugah al-‘Arabiyyah - Rina Asih Handayani; Ibnu Hadjar; Suja'i Suja'i (LISANIA: Journal of Arabic Education and Literature, 2023)
This paper aims to describe how the evaluation of learning Arabic uses the Discrepancy Evaluation Model (DEM) developed by Provus and what its effectiveness is like. The author uses a qualitative research method of literature study. The results of this paper are: First, there are three main components in the evaluation model developed by Provus, namely: 1) Standards, including a list of characteristics and qualities that are expected after the implementation of the program, 2) Performance, namely all the characteristics and qualities that have been formed as a result from program implementation, and 3) Discrepancies, namely gaps found after carrying out comparisons between Standards (S) and Performance (P). Second, these three components are then implemented in learning Arabic using five discrepancy evaluation steps, namely: Installation, Design, Process, Product and Comparison.